Site index for Prosopis alba plantations in the semi-arid chaco through mixed models - Senilliani, Maria Gracia; Bruno, Cecilia Inés; Brassiolo, Miguel Marcelo (2023)
Fil: Senilliani, Maria Gracia. Universidad Nacional de Santiago del Estero. Facultad de Ciencias Forestales; Argentina.